Neonatal developmental care in infant pain management and internalizing behaviours at 18 months in prematurely born children. (5th February 2016) - Montirosso, R.; Casini, E.; Del Prete, A.; Zanini, R.; Bellù, R.; Borgatti, R.; ,
Abstract: Background: Very preterm infants are exposed to adverse stressful experiences, which may result in long‐term behavioural outcomes. The developmental care practices, including pain management and environmental support, can minimize the effects of stress exposure. However, developmental care quality levels may vary among Neonatal Intensive Care Units (NICUs) and little is known about how differences in developmental care quality affect long‐term behavioural outcomes. The aim of this study was to examine the relation between quality levels NICUs developmental care and behaviour problems at 18 months corrected age in preterm children. Methods: The behaviour of 134 preterm children from 22 NICUs and 123 full‐term controls was examined using the questionnaire Child Behaviour Checklist 1½–5. We compared the behavioural profile of children by splitting NICUs into units with high‐ and low quality of developmental care according to two main care factors: (1) infant centered care (ICC) index, and (2) infant pain management (IPM) index. Results: Preterm children from low‐care units in IPM group reported higher scores in Internalizing Problems, compared to children from high‐care units. No differences were found between preterm children from high‐care in IPM and full‐term children. No significant IPM effect was found for externalizing problems. No significant ICC effect emerged both for internalizing and externalizing problems. Conclusions: Findings suggest that higher quality of developmental care related to infant pain management can mitigate behavioural problems at 18 months in children born preterm, to such an extent that preterm children exhibit a behavioural profile similar to that displayed by full‐term children.